Graphene modified ternary composite ultrafast curing grouting material and preparation method thereof

By introducing functional nanomaterials such as graphene and carbon nanotubes into the grouting materials, a conductive network and an interface chemical bond network are built, and an intelligent responsive expansion factor is used to solve the problems of slow curing speed, low interface bonding strength and insufficient durability of the grouting materials in the soil layer with high moisture content, and rapid curing and high-strength interface combination of the grouting materials are achieved.

CN119661187APending Publication Date: 2025-03-21CHINA MCC5 GROUP CORP LTD

Patent Information

Application Number
CN202411748881.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the soil layer with high moisture content, the existing grouting materials have slow curing speed, low interface bonding strength, and insufficient durability, which cannot meet the progress and stability requirements of underground engineering construction.

Method used

Graphene-modified ternary composite ultrafast curing grouting material is used to construct a conductive network through functionalized graphene and carbon nanotubes, combine nano-scale molecular sieve and surface-modified composite mineral blends to build a multiple cross-linking network and an interface chemical bond network, and introduce intelligent responsive expansion factors to achieve rapid curing and high-strength interface combination.

Benefits of technology

The curing time of grouting materials is shortened by 70%, the interface bonding strength is increased by 80%, and the service life is doubled, which solves the problems of slow curing speed, poor interface bonding and insufficient durability of traditional grouting materials in high moisture content soil layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661187A_ABST
    Figure CN119661187A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of grouting materials, and particularly relates to a graphene modified ternary composite ultrafast curing grouting material and a preparation method thereof. The technical scheme is as follows: the graphene modified ternary composite ultrafast curing grouting material comprises the following components: a main agent and a curing agent in a weight ratio of 4: 1, wherein the main agent is prepared from the following components in parts by weight: 30 to 33 parts of modified nano calcium silicate, 0.8 to 0.9 part of functionalized graphene, 3.8 to 4.2 parts of intelligent response type expansion factors, 2.5 to 3.0 parts of nanoscale molecular sieves and 18 to 20 parts of surface modified composite mineral admixtures; the main agent is prepared by adopting a special dispersion medium; the curing agent is prepared from the following components in parts by weight: 1.5 to 1.8 parts of amino-functionalized carbon nanotubes, 9 to 10 parts of an active site initiator, 4.5 to 5.0 parts of an interface coupling agent composite system and 2.5 to 2.8 parts of an intelligent regulation and control aid; the curing agent is prepared by a special carrier. The invention provides a graphene modified ternary composite ultrafast curing grouting material and a preparation method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of grouting materials, and in particular relates to a graphene-modified ternary composite ultrafast curing grouting material and a preparation method thereof. Background Art

[0002] With the continuous expansion of underground engineering construction, the demand for anti-floating anchor construction in soft soil layers, especially high-water content soil layers, is increasing. High-water content soil layers have the characteristics of large water holding capacity, strong permeability and low strength, which bring great challenges to grouting construction. When grouting in such soil layers, due to the high free water content in the environment, the injected slurry is severely diluted, which not only causes a large amount of material waste, but also affects the consolidation strength of the grouting body. At the same time, the ion exchange effect in a high-water content environment will interfere with the hydration process of the slurry, resulting in slow development of the grouting body strength and unable to meet the requirements of the engineering construction progress. In addition, the interface action mechanism between the existing grouting materials and the high-water content soil is relatively simple, mainly relying on mechanical bite, resulting in generally low interface bonding strength. Under long-term immersion conditions, the grouting body is also prone to softening and strength attenuation, which seriously affects the long-term stability and safety of the project. Especially under the working conditions of frequent changes in groundwater levels, the durability problem of the grouting body is more prominent.

[0003] In the field of grouting reinforcement technology for high-water content soil layers, domestic and foreign scholars have conducted a lot of research work. In the early days, ordinary silicate cement slurry was mainly used for grouting, but due to its strong compatibility with water, it was easily diluted and lost by groundwater, and the hydration reaction rate was slow, resulting in low construction efficiency. In order to improve the grouting effect, researchers developed a cement-water glass double-liquid slurry system, which adjusted the gel time of the slurry by controlling the modulus and concentration of water glass, and improved the grouting effect to a certain extent. However, this system has problems such as severe water seepage and poor durability. Subsequently, chemical grouting materials have been widely used, such as polyurethane, epoxy resin, acrylate, etc. These materials have certain rapid curing properties, but they are expensive and environmentally unfriendly. In recent years, researchers have tried to compound various admixtures in cement-based slurry, such as expansion agents, water reducers, and accelerators, to improve their engineering performance. At the same time, some scholars have proposed composite mineral admixture modification technology to improve slurry performance by adding active mineral materials such as fly ash and slag. However, these improvement measures still fail to fundamentally solve the core technical problems in grouting construction of soil layers with high water content.

[0004] Through searching, it is found that the existing similar patents are: CN112159194A, CN112707678A, CN112876160A and CN113998956A. Through analysis and comparison, it is found that the above four existing patents mainly innovate from different angles such as raw materials, two-component system, particle modification and composite reinforcement. The innovative idea of ​​patent CN112159194A is to use industrial solid waste as raw materials and improve the gelling activity by stimulating the system, which not only solves the problem of solid waste utilization, but also improves the material performance. Patent CN112707678A starts with the design of the grouting system, realizes controllable performance through two-component coordination, especially uses amine and sulfate catalysts to regulate the curing process, and achieves good mechanical properties and durability. Patent CN112876160A uses nanotechnology as a breakthrough point, and achieves the improvement of early strength and bonding performance through particle modification and the construction of multiple cross-linked networks. Patent CN113998956A is based on the engineering needs of filling goaf areas and improves the overall performance of the material through organic-inorganic composites.

[0005] There are many deficiencies in the application of existing grouting materials and construction technologies in soil layers with high water content. Traditional cement-based grouting materials lack an efficient conductive network system, which hinders electron transmission and ion migration, resulting in a slow hydration reaction rate, and the curing time often takes several hours or even longer. Although chemical grouting materials have certain rapid curing characteristics, their cross-linking reaction mechanism is too single, lacking the multiple cross-linking network structure provided by new nanomaterials such as graphene, and are easily disturbed by water molecules in a high water content environment, affecting the curing effect. The existing material system generally lacks a molecular-scale interface regulation mechanism, and the grouting body and the soil body mainly rely on simple physical bite effects, and fail to form a chemical bond network through functionalized carbon nanotubes like the present invention. This traditional interface bonding method is prone to failure under long-term immersion conditions. At the same time, conventional grouting materials lack the regulation of intelligent responsive expansion factors, and cannot achieve adaptive compensation of volume. The shrinkage deformation during the curing process often causes the grouting body to separate from the soil body. In terms of durability, due to the lack of the synergistic effect of nano-molecular sieves to form multiple protective barriers, the existing materials are prone to strength attenuation and structural damage under conditions of frequent changes in water levels. In addition, the microstructure design of traditional grouting materials is relatively rough, and they fail to construct a multi-scale interface structure through surface-modified composite mineral admixtures like the present invention, so their overall performance and service life are greatly limited. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the object of the present invention is to provide a graphene-modified ternary composite ultrafast curing grouting material and a preparation method thereof.

[0007] The technical solution adopted by the present invention is:

[0008] A graphene-modified ternary composite ultrafast curing grouting material comprises the following components in a weight ratio: main agent: curing agent = 4:1;

[0009] The main agent preparation includes the following components in parts by weight: 30-33 parts of modified nano calcium silicate, 0.8-0.9 parts of functionalized graphene, 3.8-4.2 parts of intelligent responsive expansion factor, 2.5-3.0 parts of nano-molecular sieve, and 18-20 parts of surface-modified composite mineral admixture; the main agent preparation adopts a special dispersion medium;

[0010] The preparation of the curing agent includes the following components in parts by weight: 1.5 to 1.8 parts of amino-functionalized carbon nanotubes, 9 to 10 parts of active site initiators, 4.5 to 5.0 parts of interface coupling agent composite systems, and 2.5 to 2.8 parts of intelligent control additives; the preparation of the curing agent uses a special carrier.

[0011] The present invention introduces functionalized graphene and carbon nanotubes into the grouting material system for the first time, and uses its unique conductive network to accelerate ion transmission, shortening the curing time to less than 15 minutes, fundamentally realizing the acceleration of the curing reaction. The present invention increases the interface bonding strength to more than 2.5MPa through the chemical bond network constructed by functionalized nanomaterials; the intelligent response expansion factor is used to achieve precise control of volume deformation, and the shrinkage rate is reduced to less than 0.05%; the construction of multiple protective barriers prolongs the service life of the material by more than double. The present invention proposes a new reaction mechanism of "multiple cross-linked networks + interface chemical bonding + intelligent response", which not only solves the problem of slow curing speed of traditional grouting materials, but also achieves a significant improvement in interface bonding strength. From the application effect, the present invention has achieved breakthrough indicators such as shortening the curing time by 70% and increasing the interface bonding strength by 80%.

[0012] As a preferred embodiment of the present invention, the modified nano calcium silicate generally has a particle size distribution of 50 to 100 nm and has a core-shell structure; the functionalized graphene uses graphene oxide as a raw material, and the sheet thickness is controlled at 3 to 5 nm; the intelligent responsive expansion factor uses modified calcium sulfoaluminate, and the particle size distribution is 2 to 5 μm; the nano-scale molecular screening uses NaY type molecular sieve, and the pore size is 0.7 nm; the surface modified composite mineral admixture is composed of 80% by mass of granulated blast furnace slag powder and 20% by mass of modified metakaolin; the special dispersion medium uses a polycarboxylic acid-based high-performance water reducer, and the concentration is 30% aqueous solution.

[0013] As a preferred embodiment of the present invention, the diameter of the amino-functionalized carbon nanotubes is 20 to 30 nm, and the length is 0.5 to 2 μm; the active site initiator is a modified polyether amine with a molecular weight of 2000 to 3000; the interface coupling agent composite system is composed of a silane coupling agent KH550 and a titanate coupling agent in a mass ratio of 3:1; the intelligent control auxiliary agent is a pH-sensitive polymer with a molecular weight of 5000 to 8000; and the special carrier is a modified epoxy resin emulsion.

[0014] A method for preparing a graphene-modified ternary composite ultrafast curing grouting material comprises the following steps:

[0015] S1: Metering ratio: The mass ratio of the main agent to the curing agent is strictly controlled at 4:1, and a precision metering pump system is used for quantitative delivery;

[0016] S2: Dynamic mixing: Use a spiral dynamic mixer to quickly mix the main agent and curing agent. The mixer speed is set to 2000r / min, the mixing temperature is controlled at 20±2℃, and the residence time is controlled at 3-5s;

[0017] S3: Quality control: Each batch is sampled for testing of density, viscosity and pH value. The density is controlled at 1.45±0.05g / cm3, the viscosity is controlled at 80±10Pa·s (25℃), and the pH value is controlled at 11.5±0.5.

[0018] As a preferred embodiment of the present invention, the preparation of the main agent comprises the following steps:

[0019] T1: Pre-dispersion treatment: Add modified nano calcium silicate into a special dispersion medium, use a high-speed shearing machine for shear dispersion, set the speed to 6000-8000r / min, and the dispersion time is 15min; at the same time, add functionalized graphene into another special dispersion medium, use ultrasonic dispersion technology for treatment, ultrasonic power 400W, frequency 25kHz, treatment time 30min;

[0020] T2: One-time compounding: slowly pour the dispersed graphene solution into the nano-calcium silicate slurry, and mix them by mechanical stirring and ultrasonic synergistic dispersion technology; the stirring speed is controlled at 500-600r / min, and ultrasonic waves are applied at the same time, with an ultrasonic power of 200W, an ultrasonic frequency of 20kHz, and a mixing time of 20min; the system temperature is controlled at 25±2℃ by a water bath;

[0021] T3: Secondary compounding: the intelligent responsive expansion factor and the nano-scale molecular sieve were mixed, and dry activated by a rocking vibration ball mill, with a ball-to-material ratio of 10:1 and a ball milling time of 2 hours; the ball-milled mixed powder was slowly added to the primary composite slurry, and mechanical stirring was continued at a speed of 800 r / min for 15 minutes;

[0022] T4: Final compounding: Add surface-modified composite mineral admixtures to the system and mix them using a double-shaft planetary mixer at a speed of 300r / min for 10min; during the mixing process, maintain a vacuum degree of -0.06MPa for vacuum treatment to eliminate bubbles; finally, filter through a 100-mesh sieve to obtain a uniform main agent slurry.

[0023] As a preferred embodiment of the present invention, the preparation process of the functionalized graphene is:

[0024] Graphene oxide was dispersed in deionized water at a concentration of 2 mg / mL and treated by ultrasonic-electrochemical composite exfoliation technology; ultrasonic power 600 W, frequency 40 kHz, time 2 h; electrochemical treatment voltage 3.0 V, current density 20 mA / cm 2 , time 30min; then the surface functional groups were modified by using silica coating technology, the reaction temperature was 60℃, the time was 4h, and finally the functionalized graphene was obtained by vacuum drying.

[0025] As a preferred embodiment of the present invention, the preparation process of the modified nano calcium silicate is:

[0026] Modified nano-calcium silicate was prepared by the reverse microemulsion method; calcium nitrate and sodium silicate were dissolved in deionized water, respectively, with a concentration of 0.1 mol / L; the sodium silicate solution was slowly added dropwise to n-hexane containing a surfactant under stirring at a speed of 800 r / min to form an oil-in-water microemulsion; the surfactant was sodium dodecylbenzene sulfonate with a concentration of 0.05 mol / L; calcium nitrate solution was then added, the dropwise acceleration rate was controlled to be 2 mL / min, the reaction temperature was 25°C, and the reaction time was 2 h; the product was centrifuged, washed, dried, and then calcined at 180°C for 2 h.

[0027] As a preferred embodiment of the present invention, the preparation process of the intelligent responsive expansion factor is:

[0028] An intelligent responsive expansion factor was prepared by in-situ polymerization technology; acrylamide and N-isopropylacrylamide were dissolved in deionized water at a mass ratio of 3:1, and the total monomer concentration was 30wt%; 0.5wt% of the cross-linking agent N,N'-methylenebisacrylamide and 0.2wt% of the initiator ammonium persulfate were added, and the reaction was carried out at 70°C for 4h under nitrogen protection; the product was dialyzed and freeze-dried to obtain a temperature-sensitive / pH-sensitive intelligent responsive expansion factor.

[0029] As a preferred embodiment of the present invention, the preparation of the curing agent comprises the following steps:

[0030] Y1: Pretreatment: Add amino-functionalized carbon nanotubes into a special carrier and use high shear dispersion technology for treatment at a speed of 10,000 r / min for 20 min; use an ice water bath to control the temperature at 15±2°C to avoid local overheating;

[0031] Y2: Composite stirring: Add the active site initiator and the interface coupling agent composite system to the dispersion in sequence, and mix them by mechanical stirring at a speed of 400r / min for 15min; finally, add the intelligent control auxiliary agent and continue stirring for 10min; the whole process is carried out under nitrogen protection.

[0032] As a preferred embodiment of the present invention, it also includes a maintenance system:

[0033] Preliminary maintenance: temperature 20±2℃; relative humidity above 95%; time is 24 hours;

[0034] Post-maintenance: temperature 20±2℃; relative humidity 60±5%; time is 27 days.

[0035] The beneficial effects of the present invention are:

[0036] The present invention introduces functionalized graphene and carbon nanotubes into the grouting material system for the first time, and uses its unique conductive network to accelerate ion transmission, shortening the curing time to less than 15 minutes, fundamentally realizing the acceleration of the curing reaction. The present invention increases the interface bonding strength to more than 2.5MPa through the chemical bond network constructed by functionalized nanomaterials; the intelligent response expansion factor is used to achieve precise control of volume deformation, and the shrinkage rate is reduced to less than 0.05%; the construction of multiple protective barriers prolongs the service life of the material by more than double. The present invention proposes a new reaction mechanism of "multiple cross-linked networks + interface chemical bonding + intelligent response", which not only solves the problem of slow curing speed of traditional grouting materials, but also achieves a significant improvement in interface bonding strength. From the application effect, the present invention has achieved breakthrough indicators such as shortening the curing time by 70% and increasing the interface bonding strength by 80%. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is a flow chart of the method of the present invention;

[0038] Figure 2 It is a flow chart for preparation of pre-materials. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0040] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0041] like Figure 1 and Figure 2 As shown, the graphene modified ternary composite ultrafast curing grouting material of this embodiment includes the following components in the following weight ratio: main agent: curing agent = 4:1.

[0042] Among them, the main agent composition design uses nano-scale modified calcium silicate as the main body, combined with multifunctional synergistic components. The content of modified nano calcium silicate is controlled at 30-33%, synthesized by sol-gel method, with a particle size distribution of 50-100nm, and has a core-shell structure. The amount of functionalized graphene is 0.8-0.9%, graphene oxide is selected as the raw material, and it is prepared by hydrazine reduction method, and the thickness of the sheet is controlled at 3-5nm. The intelligent responsive expansion factor uses modified calcium sulfoaluminate, the addition amount is 3.8-4.2%, and the particle size distribution is 2-5μm. NaY type molecular sieve is used for nano-scale molecular screening, with a pore size of 0.7nm and an addition amount of 2.5-3.0%. The surface modified composite mineral admixture is composed of granulated blast furnace slag powder (80%) and modified metakaolin (20%), with a total amount of 18-20%. The special dispersion medium uses a polycarboxylic acid-based high-performance water reducer with a concentration of 30% aqueous solution.

[0043] The curing agent adopts multi-component compounding technology. The dosage of amino-functionalized carbon nanotubes is 1.5-1.8%, the tube diameter is 20-30nm, and the length is 0.5-2μm. The active site initiator uses modified polyether amine with a molecular weight of 2000-3000 and an addition amount of 9-10%. The interface coupling agent composite system is composed of silane coupling agent KH550 and titanate coupling agent, with a mass ratio of 3:1 and a total amount of 4.5-5.0%. The intelligent control auxiliary agent uses pH-sensitive polymers with a molecular weight of 5000-8000 and a dosage of 2.5-2.8%. The special carrier uses modified epoxy resin emulsion.

[0044] The preparation method of the graphene-modified ternary composite ultrafast curing grouting material of the present invention comprises the following steps:

[0045] S1: Metering ratio: The mass ratio of the main agent to the curing agent is strictly controlled at 4:1, and a precision metering pump system is used for quantitative delivery;

[0046] S2: Dynamic mixing: Use a spiral dynamic mixer to quickly mix the main agent and curing agent. The mixer speed is set to 2000r / min, the mixing temperature is controlled at 20±2℃, and the residence time is controlled at 3-5s;

[0047] S3: Quality control: Each batch is sampled to test density, viscosity and pH value, and the density is controlled at 1.45±0.05g / cm 3 , viscosity is controlled at 80±10Pa·s (25℃), and pH value is controlled at 11.5±0.5.

[0048] Wherein, the preparation of the main agent comprises the following steps:

[0049] T1: Pre-dispersion treatment: Add modified nano calcium silicate into a special dispersion medium, use a high-speed shearing machine for shear dispersion, set the speed to 6000-8000r / min, and the dispersion time is 15min; at the same time, add functionalized graphene into another special dispersion medium, use ultrasonic dispersion technology for treatment, ultrasonic power 400W, frequency 25kHz, treatment time 30min;

[0050] T2: One-time compounding: slowly pour the dispersed graphene solution into the nano-calcium silicate slurry, and mix them by mechanical stirring and ultrasonic synergistic dispersion technology; the stirring speed is controlled at 500-600r / min, and ultrasonic waves are applied at the same time, with an ultrasonic power of 200W, an ultrasonic frequency of 20kHz, and a mixing time of 20min; the system temperature is controlled at 25±2℃ by a water bath;

[0051] T3: Secondary compounding: the intelligent responsive expansion factor and the nano-scale molecular sieve were mixed, and dry activated by a rocking vibration ball mill, with a ball-to-material ratio of 10:1 and a ball milling time of 2 hours; the ball-milled mixed powder was slowly added to the primary composite slurry, and mechanical stirring was continued at a speed of 800 r / min for 15 minutes;

[0052] T4: Final compounding: Add surface-modified composite mineral admixtures to the system and mix them using a double-shaft planetary mixer at a speed of 300r / min for 10min; during the mixing process, maintain a vacuum degree of -0.06MPa for vacuum treatment to eliminate bubbles; finally, filter through a 100-mesh sieve to obtain a uniform main agent slurry.

[0053] In the main agent, the preparation process of functionalized graphene is:

[0054] Graphene oxide was dispersed in deionized water at a concentration of 2 mg / mL and treated by ultrasonic-electrochemical composite exfoliation technology; ultrasonic power 600 W, frequency 40 kHz, time 2 h; electrochemical treatment voltage 3.0 V, current density 20 mA / cm 2 , time 30min; then the surface functional groups were modified by using silica coating technology, the reaction temperature was 60℃, the time was 4h, and finally the functionalized graphene was obtained by vacuum drying.

[0055] In the main agent, the preparation process of modified nano calcium silicate is:

[0056] Modified nano-calcium silicate was prepared by the reverse microemulsion method; calcium nitrate and sodium silicate were dissolved in deionized water, respectively, with a concentration of 0.1 mol / L; the sodium silicate solution was slowly added dropwise to n-hexane containing a surfactant under stirring at a speed of 800 r / min to form an oil-in-water microemulsion; the surfactant was sodium dodecylbenzene sulfonate with a concentration of 0.05 mol / L; calcium nitrate solution was then added, the dropwise acceleration rate was controlled to be 2 mL / min, the reaction temperature was 25°C, and the reaction time was 2 h; the product was centrifuged, washed, dried, and then calcined at 180°C for 2 h.

[0057] In the main agent, the preparation process of the intelligent response expansion factor is:

[0058] An intelligent responsive expansion factor was prepared by in-situ polymerization technology; acrylamide and N-isopropylacrylamide were dissolved in deionized water at a mass ratio of 3:1, and the total monomer concentration was 30wt%; 0.5wt% of the cross-linking agent N,N'-methylenebisacrylamide and 0.2wt% of the initiator ammonium persulfate were added, and the reaction was carried out at 70°C for 4h under nitrogen protection; the product was dialyzed and freeze-dried to obtain a temperature-sensitive / pH-sensitive intelligent responsive expansion factor.

[0059] Wherein, the preparation of the curing agent comprises the following steps:

[0060] Y1: Pretreatment: Add amino-functionalized carbon nanotubes into a special carrier and use high shear dispersion technology for treatment at a speed of 10,000 r / min for 20 min; use an ice water bath to control the temperature at 15±2°C to avoid local overheating;

[0061] Y2: Composite stirring: Add the active site initiator and the interface coupling agent composite system to the dispersion in sequence, and mix them by mechanical stirring at a speed of 400r / min for 15min; finally, add the intelligent control auxiliary agent and continue stirring for 10min; the whole process is carried out under nitrogen protection.

[0062] The method of the present invention also includes a maintenance regime:

[0063] Preliminary maintenance: temperature 20±2℃; relative humidity above 95%; time is 24 hours;

[0064] Post-maintenance: temperature 20±2℃; relative humidity 60±5%; time is 27 days.

[0065] Working mechanism:

[0066] During the rapid solidification process, the material exhibits a unique multi-network synergistic effect. The functionalized graphene sheets and amino carbon nanotubes form an interpenetrating conductive network structure in space. This network is like a well-designed three-dimensional electron highway, which significantly improves the transmission efficiency of electrons in the system. 2+ and SiO4 2- When these key ions migrate rapidly and directionally on this "highway", they can reach the reaction site faster, accelerating the process of the hydration reaction. At the same time, chemical bonding occurs between the active sites on the surface of nano-calcium silicate and the amino groups on the carbon nanotubes to form a cross-linked network, which is like building a strong three-dimensional scaffold inside the material, providing excellent mechanical properties for the entire system. It is particularly worth mentioning that the addition of the intelligent responsive expansion factor enables the material to adapt to the environment. It can sense the pH value and temperature changes of the local environment, and accurately compensate for the shrinkage during the hydration process through controllable volume expansion, ensuring the volume stability of the material.

[0067] In terms of interface enhancement, the material forms a complex chemical bond network system. The interface coupling agent plays the role of a "molecular bridge". By forming silicon-oxygen bonds and titanium-oxygen bonds, the inorganic components and organic components are tightly connected together to construct a three-dimensional cross-linked network structure. Functionalized graphene sheets form a stable conductive network with carbon nanotubes through π-π stacking, which not only provides an electron transmission channel, but also enhances the overall mechanical properties of the material. More importantly, the carboxyl groups on the surface of graphene can complex with metal ions in the soil to form stable chemical bonds. This multiple chemical bonding mechanism significantly improves the interface bonding strength between the grouting body and the soil.

[0068] The improved durability of the material is due to the multiple protective barriers it forms. The nano-molecular sieve gradually forms a regular three-dimensional skeleton structure during the hydration process. This structure is like a molecular-level filter that can effectively block the penetration of harmful ions. The surface-modified composite mineral admixture generates a large amount of secondary CSH gel through volcanic ash reaction. These gels accurately fill the microscopic pores in the material and significantly reduce the permeability of the material. The intelligent response component gives the material the ability to adapt to environmental changes and respond to fluctuations in the external environment through reversible volume changes. This is like installing an "adaptive system" on the material that can actively maintain the stability of the structure. The synergistic effect of these protection mechanisms enables the material to exhibit excellent durability in complex engineering environments.

[0069] In practical applications, these three mechanisms work in synergy and are inseparable. The conductive network formed during the rapid solidification process provides the necessary reaction conditions for interfacial chemical bonding, and the formation of the chemical bond network further stabilizes the microstructure of the material. At the same time, the construction of multiple protective barriers not only protects these microstructures, but also maintains the long-term stability of the material through an intelligent response mechanism. This synergistic effect enables the material to achieve the comprehensive performance of rapid solidification, strong interfacial bonding, and long-term stability in high-water content soil layers.

[0070] Example 1: Mainly optimize fast curing performance:

[0071] In the main agent, the content of nano-modified calcium silicate is 32.5%, and the particle size is controlled at 75-85nm. The amount of functionalized graphene is 0.85%, and the thickness of the flake is 3.5nm. The intelligent responsive expansion factor uses modified calcium sulfoaluminate with a particle size of 3-4μm, and the amount is 4.0%. The amount of nano-molecular sieve added is 2.7%. The total amount of surface-modified composite mineral admixture is 19%, of which the ratio of granulated blast furnace slag powder to modified metakaolin is 75:25. In curing agent B, the amount of amino-functionalized carbon nanotubes is 1.6%, the tube diameter is 25nm, the length is 1.5μm, and the amount of active site initiator is 9.5%. In the preparation process, the ultrasonic power is increased to 650W during the graphene functionalization treatment, and the electrochemical treatment voltage is increased to 3.2V. The ultrasonic power is increased to 250W in the first composite stage, and the mixing time is extended to 25 minutes. The formula ultimately achieved an initial setting time of 12 minutes and a 28-day compressive strength of 38 MPa.

[0072] Table 1 is the test result table of Example 1:

[0073]

[0074]

[0075] Embodiment 2: Focus on interface bonding performance:

[0076] In the main agent, the content of nano-modified calcium silicate is 31.5%, and the particle size distribution is 60-90nm. The amount of functionalized graphene is 0.88%, and the thickness of the flakes is 4nm. The amount of intelligent responsive expansion factor is 4.1%, and the particle size is 2.5-4.5μm. The total amount of surface-modified composite mineral admixtures is 19.5%, and the ratio of slag powder to kaolin is adjusted to 70:30. In curing agent B, the content of amino-functionalized carbon nanotubes is increased to 1.7%, the total amount of the interface coupling agent composite system is increased to 4.8%, and the ratio of silane to titanate coupling agent is adjusted to 3.5:1. The amount of intelligent control additives is increased to 2.7%. In terms of process, the speed of the high-speed shearing machine is increased to 7500r / min during pre-dispersion treatment, and the time is extended to 20 minutes. The ball milling time in the secondary composite stage is extended to 2.5 hours, and the ball-to-material ratio is increased to 12:1. This formula achieves an interface bonding strength of 2.8MPa and a permeability coefficient of 8×10 -9 cm / s.

[0077] Table 2 is the test result table of Example 2:

[0078] Performance Indicators Test results Initial setting time 14 minutes 28 days compressive strength 36MPa Interface bonding strength 2.8MPa Volume shrinkage 0.042% Permeability coefficient <![CDATA[8.0×10 -9 cm / s]]> Durability cycles 315 times Mass density <![CDATA[1.46g / cm 3 ]]> Viscosity (25℃) 82Pa·s pH 11.4

[0079] Example 3: Emphasis on durability:

[0080] In the main agent, the content of nano-modified calcium silicate is 33%, which is prepared by the improved sol-gel method, and the particle size is controlled at 55-85nm. The dosage of functionalized graphene is 0.89%, and the intelligent responsive expansion factor uses a product with a higher degree of modification, with an dosage of 4.2%. The nano-molecular sieve is added after surface modification, with a content of 2.8%. In curing agent B, amino-functional carbon nanotubes use surface grafted modified products with a content of 1.75%. The total amount of the interface coupling agent system is 4.9%, and a small amount of borate coupling agent is introduced at the same time. In terms of the preparation process, vacuum degassing treatment is added after one compounding, and the vacuum degree is -0.08MPa. In the final compounding stage, the stirring time is extended to 15 minutes, and a three-stage screening process is adopted. The formula achieves 350 durability cycles, and the strength retention rate reaches 92% after immersion in water for 28 days.

[0081] Table 3 is the test result table of Example 3:

[0082] Performance Indicators Test results Initial setting time 13 minutes 28 days compressive strength 35MPa Interface bonding strength 2.5MPa Volume shrinkage 0.045% Permeability coefficient <![CDATA[8.5×10 -9 cm / s]]> Durability cycles 350 times Strength retention after 28 days of immersion in water 92% Freeze-thaw cycles 150 times Mass density <![CDATA[1.44g / cm 3 ]]> Viscosity (25℃) 85Pa·s pH 11.6

[0083] These three embodiments specifically optimize material formulations and process parameters, achieving performance breakthroughs in rapid curing, interface bonding, and durability, respectively, and providing reliable technical solutions for engineering applications under different working conditions.

[0084] In terms of material system design, the design concept of "multiple cross-linked networks + interfacial chemical bonding + intelligent response" was innovatively proposed. By using nano-scale modified calcium silicate (30-33%) as the main body, functionalized graphene (0.8-0.9%) and amino carbon nanotubes (1.5-1.8%) to construct a conductive network, the rapid hydration reaction was achieved. At the same time, a silane / titanate composite coupling system (4.5-5.0%) was used to establish an interfacial chemical bond network, and an intelligent responsive expansion factor (3.8-4.2%) was introduced to achieve volume compensation. This multi-component synergistic mechanism is significantly innovative.

[0085] In terms of preparation technology, the ultrasonic-electrochemical composite exfoliation technology was invented to process graphene, the inverse microemulsion method was innovatively used to prepare nano calcium silicate, and the in-situ polymerization process of intelligent response components was developed. In particular, in the compounding process, the gradient mixing process of pre-dispersion, primary compounding, secondary compounding and final compounding ensures the uniform dispersion and full reaction of each functional component. This refined process control system has important technical value.

[0086] In terms of performance indicators, the material has achieved an initial setting time of no more than 15 minutes, a 28-day compressive strength of more than 35MPa, an interface bonding strength of more than 2.5MPa, a volume shrinkage rate of less than 0.05%, and a permeability coefficient of less than 10. -8 cm / s level, and the durability cycle number exceeds 300 times. These indicators have made a qualitative leap compared with traditional grouting materials, reflecting significant technological progress.

[0087] In terms of engineering application effects, the material shortens the curing time by 70%, increases the interface bonding strength by 80%, reduces the shrinkage by 85%, and doubles the service life. This comprehensive performance improvement solves the key problems of slow curing speed, poor interface bonding, and insufficient durability in the grouting construction of high-water content soil layers, providing reliable technical support for underground engineering construction.

[0088] The core protection points of this invention should include: the preparation method of functionalized nanomaterials and their component ratios, the synthesis process of intelligent response components, the multi-stage mixing preparation process of composite materials, and the rapid curing mechanism based on multiple network synergy.

[0089] The present invention is not limited to the above-mentioned optional implementation modes. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that fall within the scope defined by the claims of the present invention fall within the protection scope of the present invention.

Claims

1. A graphene-modified ternary composite ultrafast curing grouting material, characterized in that: The composition comprises the following components in a weight ratio: main agent: curing agent = 4:1; The main agent preparation includes the following components in parts by weight: 30-33 parts of modified nano calcium silicate, 0.8-0.9 parts of functionalized graphene, 3.8-4.2 parts of intelligent responsive expansion factor, 2.5-3.0 parts of nano-molecular sieve, and 18-20 parts of surface-modified composite mineral admixture; the main agent preparation adopts a special dispersion medium; The preparation of the curing agent includes the following components in parts by weight: 1.5 to 1.8 parts of amino-functionalized carbon nanotubes, 9 to 10 parts of active site initiators, 4.5 to 5.0 parts of interface coupling agent composite systems, and 2.5 to 2.8 parts of intelligent control additives; the preparation of the curing agent uses a special carrier.

2. The graphene-modified ternary composite ultrafast curing grouting material according to claim 1, characterized in that: The modified nano calcium silicate generally has a particle size distribution of 50 to 100 nm and has a core-shell structure; the functionalized graphene uses graphene oxide as a raw material, and the sheet thickness is controlled at 3 to 5 nm; the intelligent responsive expansion factor uses modified calcium sulfoaluminate, and the particle size distribution is 2 to 5 μm; the nano-scale molecular screening uses NaY type molecular sieve, and the pore size is 0.7 nm; the surface modified composite mineral admixture is composed of 80% by mass of granulated blast furnace slag powder and 20% by mass of modified metakaolin; the special dispersing medium uses a polycarboxylic acid-based high-performance water reducer, and the concentration is a 30% aqueous solution.

3. The graphene-modified ternary composite ultrafast curing grouting material according to claim 1, characterized in that: The diameter of the amino-functionalized carbon nanotubes is 20 to 30 nm, and the length is 0.5 to 2 μm; the active site initiator is a modified polyether amine with a molecular weight of 2000 to 3000; the interface coupling agent composite system is composed of a silane coupling agent KH550 and a titanate coupling agent in a mass ratio of 3:1; the intelligent control auxiliary agent is a pH-sensitive polymer with a molecular weight of 5000 to 8000; and the special carrier is a modified epoxy resin emulsion.

4. A method for preparing a graphene-modified ternary composite ultrafast curing grouting material, used for preparing a graphene-modified ternary composite ultrafast curing grouting material according to claim 1, characterized in that: The following steps are involved: S1: Metering ratio: The mass ratio of the main agent to the curing agent is strictly controlled at 4:1, and a precision metering pump system is used for quantitative delivery; S2: Dynamic mixing: Use a spiral dynamic mixer to quickly mix the main agent and curing agent. The mixer speed is set to 2000r / min, the mixing temperature is controlled at 20±2℃, and the residence time is controlled at 3-5s; S3: Quality control: Each batch is sampled to test density, viscosity and pH value, and the density is controlled at 1.45±0.05g / cm 3 , viscosity is controlled at 80±10Pa·s (25℃), and pH value is controlled at 11.5±0.

5.

5. The method for preparing a graphene-modified ternary composite ultrafast curing grouting material according to claim 4, characterized in that: The preparation of the main agent comprises the following steps: T1: Pre-dispersion treatment: Add modified nano calcium silicate into a special dispersion medium, use a high-speed shearing machine for shear dispersion, set the speed to 6000-8000r / min, and the dispersion time is 15min; at the same time, add functionalized graphene into another special dispersion medium, use ultrasonic dispersion technology for treatment, ultrasonic power 400W, frequency 25kHz, treatment time 30min; T2: One-time compounding: slowly pour the dispersed graphene solution into the nano-calcium silicate slurry, and mix them by mechanical stirring and ultrasonic synergistic dispersion technology; the stirring speed is controlled at 500-600r / min, and ultrasonic waves are applied at the same time, with an ultrasonic power of 200W, an ultrasonic frequency of 20kHz, and a mixing time of 20min; the system temperature is controlled at 25±2℃ by a water bath; T3: Secondary compounding: the intelligent responsive expansion factor and the nano-scale molecular sieve were mixed, and dry activated by a rocking vibration ball mill, with a ball-to-material ratio of 10:1 and a ball milling time of 2 hours; the ball-milled mixed powder was slowly added to the primary composite slurry, and mechanical stirring was continued at a speed of 800 r / min for 15 minutes; T4: Final compounding: Add surface-modified composite mineral admixtures to the system and mix them using a double-shaft planetary mixer at a speed of 300r / min for 10min; during the mixing process, maintain a vacuum degree of -0.06MPa for vacuum treatment to eliminate bubbles; finally, filter through a 100-mesh sieve to obtain a uniform main agent slurry.

6. The method for preparing a graphene-modified ternary composite ultrafast curing grouting material according to claim 5, characterized in that: The preparation process of the functionalized graphene is: Graphene oxide was dispersed in deionized water at a concentration of 2 mg / mL and treated by ultrasonic-electrochemical composite exfoliation technology; ultrasonic power 600 W, frequency 40 kHz, time 2 h; electrochemical treatment voltage 3.0 V, current density 20 mA / cm 2 , time 30min; then the surface functional groups were modified by using silica coating technology, the reaction temperature was 60℃, the time was 4h, and finally the functionalized graphene was obtained by vacuum drying.

7. The method for preparing a graphene-modified ternary composite ultrafast curing grouting material according to claim 5, characterized in that: The preparation process of the modified nano calcium silicate is: Modified nano-calcium silicate was prepared by the reverse microemulsion method; calcium nitrate and sodium silicate were dissolved in deionized water, respectively, with a concentration of 0.1 mol / L; the sodium silicate solution was slowly added dropwise to n-hexane containing a surfactant under stirring at a speed of 800 r / min to form an oil-in-water microemulsion; the surfactant was sodium dodecylbenzene sulfonate with a concentration of 0.05 mol / L; calcium nitrate solution was then added, the dropwise acceleration rate was controlled to be 2 mL / min, the reaction temperature was 25°C, and the reaction time was 2 h; the product was centrifuged, washed, dried, and then calcined at 180°C for 2 h.

8. The method for preparing a graphene-modified ternary composite ultrafast curing grouting material according to claim 5, characterized in that: The preparation process of the intelligent responsive expansion factor is as follows: An intelligent responsive expansion factor was prepared by in-situ polymerization technology; acrylamide and N-isopropylacrylamide were dissolved in deionized water at a mass ratio of 3:1, and the total monomer concentration was 30wt%; 0.5wt% of the cross-linking agent N,N'-methylenebisacrylamide and 0.2wt% of the initiator ammonium persulfate were added, and the reaction was carried out at 70°C for 4h under nitrogen protection; the product was dialyzed and freeze-dried to obtain a temperature-sensitive / pH-sensitive intelligent responsive expansion factor.

9. The method for preparing a graphene-modified ternary composite ultrafast curing grouting material according to claim 4, characterized in that: Preparation of the curing agent The following steps are involved: Y1: Pretreatment: Add amino-functionalized carbon nanotubes into a special carrier and use high shear dispersion technology for treatment at a speed of 10,000 r / min for 20 min. Use an ice water bath to control the temperature at 15±2°C to avoid local overheating. Y2: Composite stirring: Add the active site initiator and the interface coupling agent composite system to the dispersion in sequence, and mix them by mechanical stirring at a speed of 400r / min for 15min; finally, add the intelligent control auxiliary agent and continue stirring for 10min; the whole process is carried out under nitrogen protection.

10. The method for preparing a graphene-modified ternary composite ultrafast curing grouting material according to claim 4, characterized in that: It also includes the maintenance system: Preliminary maintenance: temperature 20±2℃; relative humidity above 95%; time is 24 hours; Post-maintenance: temperature 20±2℃; relative humidity 60±5%; time is 27 days.

Citation Information

Patent Citations

  • Solid waste foundation grouting material suitable for reinforcing bearing capacity of existing pile foundation and preparation method

    CN112159194A

  • High-elasticity grouting material as well as preparation method and application thereof

    CN112707678A

  • Anchor rod grouting material for deep foundation pit construction and preparation method thereof

    CN112876160A

  • Grouting material and preparation method thereof

    CN113998956A

Cited By

  • Grouting method based on graphene cement-based material in deep underground space

    CN121952602A

  • Quick-setting admixture for mining filling and plugging material and preparation method of quick-setting admixture

    CN122145068A